(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with a problem of this kind of punishment, the death penalty. The author traces the historical development and provides a legal analysis of the most rigorous and at the same time the ancient form of punishment known to the criminal law of modern states. Emphasis on the relation of religion to the death penalty. Formulated by the author’s position on the phased abolition of the death penalty in Kazakhstan. Key words: criminal punishment, the death penalty, the moratorium, the referendum, the abolition of the death penalty.